Acute transient encephalomyelitis involving bilateral basal ganglia and internal capsules as manifestation of primary human immunodeficiency virus infection. Issue 3 (28th December 2014) - Tamura, Akiko; Shirano, Michinori; Shimono, Taro; Takeda, Akitoshi; Tsutada, Tsuyoshi; Shimada, Hiroyuki; Itoh, Yoshiaki
Abstract A 25‐year‐old homosexual man presented with influenza‐like symptoms, followed by acute transient leukoencephalomyelitis as an initial presentation of human immunodeficiency virus infection, suggestive of acute disseminated encephalomyelitis. Magnetic resonance imaging showed hyperintensity in the bilateral periventricular white matter and internal capsules on T2‐weighted images, as well as an obscured boundary of the basal ganglia, which have been reported for the first time in primary human immunodeficiency virus infection.